Bringing Maimonides to Oxford: Edward Pococke, the Mishnah, and the Porta Mosis - Williams, B (Oxford University Press, 2022)
Among the books owned by Edward Pococke (1604–1691), Regius Professor of Hebrew and Laudian Professor of Arabic at Oxford, were numerous copies of the Mishnah with Maimonides’ Commentary, including a manuscript now known to have been annotated by Maimonides himself (Bodleian Library, MS Poc. 295). This chapter considers how Pococke studied these texts and whether he realized that he owned part of Maimonides’ working copy. An analysis of Pococke’s annotated books and published works shows that he acquired texts from Aleppo, studied the Mishnah under Rabbi Jacob Roman of Constantinople, used his copies of Maimonides’ Commentary to edit excerpts for publication (Porta Mosis, 1655), and deposited manuscripts at the press to serve as printers’ copy. Pococke’s incomplete knowledge of the transmission of Maimonides’ works and the caution with which he treated the autograph emendations in MS Poc. 295 suggest that the provenance of this manuscript was unknown.